Children commute to schools in Bangalore urban and rural districts: travel pattern, behaviour and perceptions - ., Manjunatha; Uthkarsh, Pallavi Sarji; ., Gangaboraiah (International Journal Of Community Medicine And Public Health, 2020)
Background: Children form vulnerable road users during their regular school commute. School children safety is not taken into consideration before construction of road network. The total number of persons injured in India during 2015 near schools or colleges or educational institutions due to road traffic accidents are 13,270 in urban areas according to National Crime Records Bureau which is quite alarming. Current study is the first attempt in both rural and urban Karnataka towards understanding travel pattern, behaviour and perceptions among school children during commute to schools. The objectives of the present study were to assess travel pattern, behaviour and perception of school children in Bangalore urban and rural districts and to assess factors associated with travel pattern. Methods: A cross sectional study was conducted using a representative sample of schools selected by simple random sampling. Data was collected using a pre-tested, semi-structured questionnaire which was analysed using SPSS version 20. Results: Nearly 86% of school children travelled less than 5 kms to reach their schools. Nearly 39% of school children travelled alone to school. Most common mode of travel to school was by walk. Nearly 27.4% did not cross the main roads safely. Adherence to road safety behaviour was insufficient. Vehicular traffic was perceived as a major apprehension by children during school commute. Conclusions: Commute of children to schools in both urban and rural part of Bangalore was unsafe with least adherence to safety measures, which might increase their vulnerability to road traffic injuries.